The Influence of Using Whatsapp Community Channels on Weight Gain in Stunted Children in Lambaro Neujid, Aceh Besar - Nilawati; Nurhayati*; Supriyanti; Khaira, Nuswatul; Manaf, Salmiani Abdul (Journal of Health, Medicine and Nursing, 2025)
Stunting is a significant public health challenge affecting children's physical and cognitive development, with long-term consequences for human resource quality. This study aims to examine the influence of using a Whatsapp Group community on weight gain among stunted children in Lambaro Neujid Village, Peukan Bada District, Aceh Besar Regency. An analytical survey with a cross-sectional approach was conducted, involving 40 families selected through random sampling. The findings reveal that factors such as parental education, family income, maternal height, and mothers' attitudes significantly impact children's weight gain. The use of communication technology, particularly Telegram groups, proved effective in delivering education and motivating behavioral changes among mothers in childcare and nutritional fulfillment. The integration of digital media in public health intervention programs offers an innovative solution to reduce stunting rates. This study recommends optimizing the role of community health workers and sustaining government support in leveraging technology for public education. In conclusion, technology-based approaches can increase awareness and community practices in reducing stunting prevalence, supporting the national target of lowering stunting rates to 14% by 2024.